Do Pain-related Beliefs Influence Adherence to Multidisciplinary Rehabilitation?: A Systematic Review. Issue 2 (February 2016) - Thompson, Emma L.; Broadbent, Jaclyn; Bertino, Melanie D.; Staiger, Petra K.
Abstract : Objectives: To understand how pain-related cognitions predict and influence treatment retention and adherence during and after a multidisciplinary rehabilitation program. Methods: Electronic databases including Medline, CINAHL, PsycINFO, Academic Search Complete, and Scopus were used to search 3 combinations of key words: chronic pain, beliefs, and treatment adherence. Results: The search strategy yielded 591 results, with an additional 12 studies identified through reference screening. Eighty-one full-text papers were assessed for eligibility and 10 papers met the inclusion and exclusion criteria for this review. The pain-related beliefs that have been measured in relation to treatment adherence include: pain-specific self-efficacy, perceived disability, catastrophizing, control beliefs, fear-avoidance beliefs, perceived benefits and barriers, and other less commonly measured beliefs. The most common pain-related belief investigated in relation to treatment adherence was pain-related self-efficacy. Findings for the pain-related beliefs investigated among the studies were mixed. Collectively, all of the aforementioned pain-related beliefs, excluding control beliefs, were found to influence treatment adherence behaviors. Discussion: The findings suggest that treatment adherence is determined by a combination of pain-related beliefs either supporting or inhibiting chronic pain patients' ability to adhere to treatment recommendations over time. In the studies reviewed, self-efficacy appears to be the most commonly researched predictor of treatment adherence, its effects also influencing other pain-related beliefs. More refined and standardized methodologies, consistent descriptions of pain-related beliefs, and methods of measurement will improve our understanding of adherence behaviors. Abstract : Supplemental Digital Content is available in the text.